Recent development in rare earth doped phosphors for white light emitting diodes - 王育华 朱革 辛双宇 王倩 李艳艳 吴泉生 王闯 王希成 丁鑫 耿婉莹 (Journal of rare earths, 2015)
As new light sources for next-generation illumination, white light-emitting diodes（WLEDs） have been extensively developed and are commercially available due to their excellent advantages, such as high efficiency, energy-saving, compactness, long operational lifetime and environmental friendliness. Currently, WLEDs with high color rendering are mainly based on wavelength conversion by one or more phosphor materials. In this review, the recent developments of phosphors for WLEDs were introduced combined with the relative work of our group. The common methods for generating white light for blue/ultraviolet（UV） WLEDs were summarized, including：（1） optimizing the commercially used phosphors;（2） developing some new phosphors based on UV LEDs chips;（3） realizing white light emission based on single host. Moreover, some typical new developed phosphors and their luminescence properties were introduced.